The Economic Value of Carbon Stocks in PT Hutan Mulya Central Kalimantan - Fitriani, Afni; Hardiansyah, Gusti; Yani, Akhmad (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
This study aims to determine how much carbon stock is stored in logged-over areas by comparing carbon stock in virgin forests. Calculate potential biomass, carbon, carbon dioxide uptake, and economic value of CO2eq uptake in the Logged area of PT Hutan Mulya using purposive sampling data collection techniques for each plot and non-destructive methods through allometric equations. The highest carbon stock potential is in the tree-level diameter class and the location with the highest carbon stock is in the virgin forest area. Meanwhile, the logged area based on the company's establishment from 2011–2022 covering an area of 14,583 ha has a carbon stock potential of 772,537 tons C to the carbon dioxide storage value of 2,835,210.57 tons CO2eq. Based on the assumed price of USD 4.5, the potential economic value of carbon obtained by the government through carbon sales tax is IDR 85,056,317,100. The net profit obtained by the company is IDR 109,494,570,499.42. In contrast, the potential net economic value of the carbon business project scenario results in a combined logged area and virgin forest area of IDR 160,960,838,842.31 for the company and IDR 125,035,753,500 for the government.